Gender Dynamics in Medieval Courts: A Case Study of Queenship in Europe - Mendes, Bete (European Journal of Historical Research, 2024)
Purpose: The aim of the study was to assess the gender dynamics in medieval courts, a case study of queenship in Europe. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: It reveals that queens often wielded significant influence despite the predominantly patriarchal structures of their time. Queenship, though constrained by societal expectations and norms, provided a platform for women to exercise authority, shape policies, and navigate complex political landscapes. The study underscores the multifaceted nature of queenship, highlighting the interplay of gender, politics, and power within medieval courtly settings. Additionally, it sheds light on the diverse strategies employed by queens to assert their agency and leave lasting legacies amidst the challenges of their era. Implications to Theory, Practice and Policy: Gender theory, power dynamics theory and cultural studies theory may be used to anchor future studies on assessing the gender dynamics in medieval courts, a case study of queenship in Europe. Investigate the lived experiences of queens within medieval courts, including their roles, responsibilities, and limitations. Draw parallels between medieval queenship and contemporary issues of gender and leadership. Highlight the importance of historical perspectives in informing modern debates on gender equality and representation in politics.